Interdependências entre educação, ética e cidadania para uma formação emancipadora e libertadora - Ahlert, Alvori (Diálogos Latinoamericanos, 2007)
The present text defends the interdependence of education, ethics and citizenship. Each belongs to the rest as they are the three dimensions of the human being, each interdependent in the search for emancipation and freedom. This text is about the discussion of an ethics of the human being which seeks the defense of life and the production of actions and policies opposed to the ethics of the marketplace, as well as a citizenship which is not fulfilled by means of decree but expresses an active participation capable of leading education to confront actual social, political and economic realities which demand justice and political, social and economic equality. In this way, ethics and citizenship find their privileged place in education. An education which constitutes itself in ethical and political action through active citizenship where all are responsible for all.